Composite electrode for non-enzymatic glucose sensor, method of preparation and use

CN116539684BActive Publication Date: 2026-10-09NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210095408.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-26
Publication Date
2026-10-09
Estimated Expiration
2042-01-26

AI Technical Summary

Technical Problem

[0006]但上述电极中的过渡金属硫化物为晶体硫化物,晶体中由于其内部存在位错、晶界等缺陷,使材料的导电性受到一定的影响,而导电性会影响反应过程中的电子转移速率,进而影响检测葡萄糖时的催化性能

Benefits of technology

[0021] 1. The composite electrode for non-enzymatic glucose sensors of the present invention has a double-layer nanostructure. The bottom layer structure is an amorphous transition metal oxide nanotube with one end open. The nanotubes produced by using amorphous alloy as a precursor have small and uniform diameters, high aspect ratio, and large specific surface area, providing more support sites for the next step of depositing transition metal sulfides. This is conducive to the formation of a nano-spherical cluster structure with a large specific surface area and many reaction sites by the amorphous transition metal sulfides deposited on the surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116539684B_ABST
    Figure CN116539684B_ABST
Patent Text Reader

Abstract

The application provides a composite electrode for a non-enzyme glucose sensor, which has a composite structure formed by a double-layer nanostructure, the double-layer nanostructure comprising a bottom layer structure and a surface layer structure, the bottom layer structure being an amorphous transition metal oxide nanotube with one end face open, and the surface layer structure being an amorphous transition metal sulfide nanostructure, and the surface layer structure being attached to the open end face of the amorphous transition metal oxide nanotube. The application also provides a preparation method and application of the composite electrode for the non-enzyme glucose sensor. The electrode of the application is self-supported by combining the amorphous transition metal oxide nanotube and the amorphous transition metal sulfide, and the sensing performance of the glucose sensor is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterials technology, and more specifically to a composite electrode for a non-enzymatic glucose sensor, its preparation method, and its application. Background Technology

[0002] Over the past decade, the development of non-enzymatic glucose sensors has grown at a considerable pace. Noble metals such as gold and platinum, with their excellent catalytic properties and stability, were among the first to be widely used as electrode materials in these sensors. For example, Zhong Shu-lin et al. used eggshell membranes as templates to prepare a three-dimensional hierarchical porous gold network through chemical plating and calcination. They observed that the electrode exhibited good sensing performance, anti-interference capabilities, and stability for glucose. However, their high cost has significantly hindered their application.

[0003] In recent years, transition metals and transition metal oxides with nanostructures have provided a cost-effective alternative due to their large surface area and numerous active sites. For example, Huang Wei et al. synthesized NiCo2O4 hollow nanospheres using a Cu2O template via a synergistic etching and precipitation (CEP) method, and used these NiCo2O4 hollow nanospheres for glucose sensing, observing a size of 1917 μm / m² using chronoamperometry. -1 cm -2 It exhibits a linear range of 0.01–2.24 mM and a detection limit of 0.6 μM. However, due to the high optical band gap energy of the oxide, it suffers from poor conductivity and stability.

[0004] As research has progressed, scientists have discovered that transition metal sulfides outperform their oxides due to the lower electronegativity of sulfur compared to oxygen. Therefore, transition metal sulfides have attracted increasing attention due to their superior inherent properties, such as relatively low cost, abundant available sources, considerable stability, excellent electrical conductivity, and excellent catalytic activity.

[0005] When applied to non-enzymatic glucose sensors, transition metal sulfides are mainly combined with conductive support materials (such as nickel foam, copper foam, and three-dimensional KSC) to further improve their electronic conductivity, forming a hierarchical nanostructure with a large surface area and numerous active centers. Chen Ding-long et al. synthesized spherical hollow ternary nickel-cobalt sulfide spheres (NiCo2S4) using a hydrothermal method for a non-enzymatic glucose detection electrochemical sensor, achieving a glucose detection sensitivity of 858.57 μM. -1 cm -2 .

[0006] However, the transition metal sulfides in the above electrodes are crystalline sulfides. Due to defects such as dislocations and grain boundaries inside the crystal, the conductivity of the material is affected to a certain extent. The conductivity affects the electron transfer rate during the reaction process, and thus affects the catalytic performance when detecting glucose. Summary of the Invention

[0007] The purpose of this invention is to address the shortcomings of existing technologies by providing a composite electrode for non-enzymatic glucose sensors. This electrode is a self-supporting composite electrode obtained by combining amorphous transition metal oxide nanotubes and amorphous transition metal sulfides, thereby improving the sensing performance of glucose sensors.

[0008] According to a first aspect of the present invention, a composite electrode for a non-enzymatic glucose sensor is provided, the composite electrode having a composite structure formed by a double-layer nanostructure, the double-layer nanostructure comprising a bottom layer structure and a surface layer structure, the bottom layer structure being an amorphous transition metal oxide nanotube with one end face open, and the surface layer structure being a nanostructure formed by an amorphous transition metal sulfide, the surface layer structure being attached to the open end face of the amorphous transition metal oxide nanotube.

[0009] Preferably, the amorphous transition metal oxide nanotube is an amorphous ZrAlCoM-O nanotube, wherein M is Ni, Ag or Nb.

[0010] Preferably, in the nanostructure formed by the amorphous transition metal sulfide, the transition metal is one or two of Ni, Co, Cu, Fe and Mn.

[0011] Preferably, the nanostructure formed by amorphous transition metal sulfides is a nanosphere cluster structure.

[0012] According to a second aspect of the present invention, a method for preparing the aforementioned composite electrode for a non-enzymatic glucose sensor is provided, comprising the following steps:

[0013] Amorphous transition metal oxide nanotubes were prepared using an amorphous alloy containing a transition metal as a precursor; wherein the precursor was Zr. 56 Al 16 Co 28-x M x M is Ni, Ag or Nb, x = 1 to 10 at.%;

[0014] Using amorphous transition metal oxide nanotubes as a substrate, amorphous transition metal sulfides are deposited on the substrate to obtain an amorphous transition metal oxide / transition metal sulfide composite electrode; wherein the transition metal in the amorphous transition metal sulfide is one or two of Ni, Co, Cu, Fe and Mn.

[0015] Preferably, amorphous transition metal oxide nanotubes are prepared by electrochemical anodic oxidation. The specific process is as follows: weigh the corresponding elemental metal material of the precursor according to the proportion, melt it to obtain a master alloy containing transition metal, then rapidly cool and spin the master alloy through a copper roller to obtain an amorphous alloy strip, then perform constant potential polarization treatment on the amorphous alloy strip in an electrolyte, and clean it to obtain amorphous transition metal oxide nanotubes.

[0016] Preferably, the electrolyte is a glycerol solution of 0.1-1M NH4F + 5%-15% vol H2O, with a polarization potential of 30-60V and a polarization time of 10-40min.

[0017] Preferably, amorphous transition metal sulfides are deposited on a substrate using electrochemical cyclic voltammetry. The specific process is as follows: a three-electrode system is used, with amorphous transition metal oxide nanotubes as the working electrode, a Pt electrode as the counter electrode, and a saturated calomel electrode as the reference electrode. The working electrode, counter electrode, and reference electrode are placed in an aqueous solution containing transition metal salts and a sulfur source, and connected to an electrochemical workstation. Amorphous transition metal sulfides are deposited on the substrate using electrochemical cyclic voltammetry.

[0018] Preferably, the operating parameters of the electrochemical cyclic voltammetry are: voltage range of -2 to 2V, scan rate of 2 to 10mV / s, and 10 to 15 cycles; the transition metal salt is a transition metal chloride salt with a concentration of 5 to 10mM; and the sulfur source is thiourea with a concentration of 0.5 to 1M.

[0019] According to a third aspect of the present invention, the aforementioned composite electrode for a non-enzymatic glucose sensor is provided for use in a non-enzymatic glucose sensor.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0021] 1. The composite electrode for non-enzymatic glucose sensors of the present invention has a double-layer nanostructure. The bottom layer structure is an amorphous transition metal oxide nanotube with one end open. The nanotubes produced by using amorphous alloy as a precursor have small and uniform diameters, high aspect ratio, and large specific surface area, providing more support sites for the next step of depositing transition metal sulfides. This is conducive to the formation of a nano-spherical cluster structure with a large specific surface area and many reaction sites by the amorphous transition metal sulfides deposited on the surface.

[0022] Amorphous sulfides possess a long-range disordered and short-range ordered amorphous structure, resulting in a large number of unsaturated ligand atoms. This significantly improves electronic conductivity and increases the number of electrochemical active centers, exhibiting higher catalytic activity than crystalline sulfides, further enhancing their catalytic performance on glucose. The unique coral-like nanocluster morphology further increases the electrochemical active surface area of ​​the electrode, providing more active sites for glucose oxidation. Furthermore, the excellent synergistic effect of transition metal sulfides further enhances the catalytic activity on glucose, improves the sensitivity of glucose detection, and broadens the detection range.

[0023] 2. The electrode of the present invention has a self-supporting structure and can be used directly for testing, avoiding the need for pretreatment of catalytic electrode materials. It is uniformly dispersed, does not agglomerate during operation, is highly efficient, and is simple to operate and easy to repeat.

[0024] 3. The electrode material of the present invention has a simple process, low cost, short processing time, and is easy to industrialize and widely used. It has better practicality and does not require strong acid solutions in the whole process, which is environmentally friendly and beneficial to environmental protection. Attached Figure Description

[0025] Figure 1a This is a morphology diagram of the amorphous oxide nanotube ZACN-O obtained in Example 1.

[0026] Figure 1b This is a morphology diagram of the Ni-S / ZACN-O electrode obtained in Example 1.

[0027] Figure 1c This is a morphology diagram of the Ni-Co-S / ZACN-O electrode obtained in Example 6.

[0028] Figure 1d This is a morphology diagram of the Ni-Co-S / ZACN-O electrode obtained in Example 6.

[0029] Figure 1e This is a morphology diagram of the Ni-Co-S / ZACN-O electrode obtained in Example 6.

[0030] Figure 2 The images show the XRD patterns of the amorphous oxide nanotubes ZACN-O and Ni-S / ZACN-O electrodes obtained in Example 1, and the Ni-Co-S / ZACN-O electrode obtained in Example 6.

[0031] Figure 3 a is the CV curve of the amorphous oxide nanotube ZACN-O obtained in Example 1 at different scan rates (10-100mV / s) in 0.1M NaOH solution.

[0032] Figure 3b is the CV curve of the Ni-S / ZACN-O electrode obtained in Example 1 at different scan rates (10-100mV / s) in 0.1M NaOH solution.

[0033] Figure 3 c is the CV curve of the Co-S / ZACN-O electrode obtained in Example 2 at different scan rates (10-100mV / s) in 0.1M NaOH solution.

[0034] Figure 3 d is the CV curve of the Ni-Co-S / ZACN-O electrode obtained in Example 6 at different scan rates (10-100mV / s) in 0.1M NaOH solution.

[0035] Figure 3 e is the CV curve of TiCu-O obtained from the comparison in 0.1M NaOH solution at different scan rates (10-100mV / s).

[0036] Figure 4 a is a fitting curve of the sensitivity of the amorphous oxide nanotube ZACN-O obtained in Example 1 to glucose. The inset is the response current density-time curve when different concentrations of glucose are added dropwise to 0.1M NaOH solution.

[0037] Figure 4 b is a fitting curve of the sensitivity of the Ni-S / ZACN-O electrode to glucose obtained in Example 1. The inset is the response current density-time curve when different concentrations of glucose are added dropwise to 0.1M NaOH solution.

[0038] Figure 4 c is a fitting curve of the sensitivity of the Co-S / ZACN-O electrode to glucose obtained in Example 2. The inset is the response current density-time curve when different concentrations of glucose are added dropwise to 0.1M NaOH solution.

[0039] Figure 4 Figure d is a fitting curve of the sensitivity of the Ni-Co-S / ZACN-O electrode to glucose obtained in Example 6. The inset is the response current density-time curve when different concentrations of glucose are added dropwise to 0.1M NaOH solution.

[0040] Figure 4 e is a fitting curve of the sensitivity of TiCu-O to glucose obtained by comparison, and the inset is the response current density-time curve when different concentrations of glucose are added dropwise to 0.1M NaOH solution. Detailed Implementation

[0041] To better understand the technical content of the present invention, specific embodiments are described below in conjunction with the accompanying drawings.

[0042] Various aspects of the invention are described in this disclosure with reference to the accompanying drawings, in which numerous illustrative embodiments are shown. The embodiments of this disclosure are not necessarily intended to encompass all aspects of the invention. It should be understood that the various concepts and embodiments described above, as well as those described below in more detail, can be implemented in any of a number of ways.

[0043] This invention provides a composite electrode for a non-enzymatic glucose sensor, wherein coral-like amorphous transition metal sulfide nanospheres are deposited on the surface of amorphous transition metal oxide nanotubes to obtain a self-supporting composite electrode.

[0044] In an exemplary embodiment of the present invention, a composite electrode for a non-enzymatic glucose sensor is provided. The composite electrode has a composite structure formed by a double-layer nanostructure, which includes a bottom layer structure and a surface layer structure. The bottom layer structure is an amorphous transition metal oxide nanotube with one end face open, and the surface layer structure is a nanostructure formed by an amorphous transition metal sulfide. The surface layer structure is attached to the open end face of the amorphous transition metal oxide nanotube.

[0045] In a preferred embodiment, the amorphous transition metal oxide nanotubes are arranged in an array on the substrate using the corresponding amorphous alloy as the substrate, and the end face of the amorphous transition metal oxide nanotubes away from the substrate has an opening.

[0046] In a preferred embodiment, the amorphous transition metal oxide nanotube is an amorphous ZrAlCoM-O nanotube, wherein M is Ni, Ag or Nb.

[0047] In a preferred embodiment, the transition metal in the nanostructure formed by the amorphous transition metal sulfide is one or two of Ni, Co, Cu, Fe and Mn.

[0048] In a preferred embodiment, the nanostructure formed by the amorphous transition metal sulfide is a nanospherical cluster structure.

[0049] In another preferred embodiment, the transition metal sulfide is Ni-S, Co-S, Cu-S, Fe-S, Mn-S, Co-Ni-S, Co-Cu-S, or Fe-Mn-S.

[0050] In a preferred embodiment, the amorphous ZrAlCoM-O nanotubes comprise a plurality of ZrAlCoM-O nanotubes, which are neatly arranged into a nanotube array structure.

[0051] In another exemplary embodiment, a method for preparing the aforementioned composite electrode for a non-enzymatic glucose sensor is provided, comprising the following steps:

[0052] Amorphous transition metal oxide nanotubes were prepared using an amorphous alloy containing a transition metal as a precursor; wherein the precursor was Zr. 56 Al 16 Co 28-x M x M is Ni, Ag or Nb, x = 1 to 10 at.%;

[0053] Using amorphous transition metal oxide nanotubes as a substrate, amorphous transition metal sulfides are deposited on the substrate to obtain an amorphous transition metal oxide / transition metal sulfide composite electrode; wherein the transition metal in the amorphous transition metal sulfide is one or two of Ni, Co, Cu, Fe and Mn.

[0054] In a preferred embodiment, amorphous transition metal oxide nanotubes are prepared by electrochemical anodic oxidation. The specific process is as follows: metal elemental materials corresponding to the precursor are weighed in proportion, smelted to obtain a transition metal master alloy, and then the master alloy is rapidly cooled and spun through a copper roller to obtain an amorphous alloy strip. The amorphous alloy strip is then subjected to constant potential polarization treatment in an electrolyte and cleaned to obtain amorphous transition metal oxide nanotubes.

[0055] In a preferred embodiment, the electrolyte is a glycerol solution of 0.1–1 M NH4F + 5%–15% vol H2O, the polarization potential is 30–60 V, and the polarization time is 10–40 min.

[0056] An amorphous transition metal oxide nanotube structure based on an amorphous alloy strip is formed by electrochemical anodic oxidation. The amorphous transition metal oxide nanotubes are arranged in an array on the upper and lower surfaces of the amorphous transition metal alloy strip, forming a unique sandwich-like sandwich structure. This sandwich-like substrate is beneficial for providing high conductivity and also provides more active sites for the deposition of amorphous transition metal sulfides.

[0057] In a preferred embodiment, amorphous transition metal sulfides are deposited on a substrate using electrochemical cyclic voltammetry. The specific process is as follows: a three-electrode system is used, with amorphous transition metal oxide nanotubes as the working electrode, a Pt electrode as the counter electrode, and a saturated calomel electrode as the reference electrode. The working electrode, counter electrode, and reference electrode are placed in an aqueous solution containing transition metal salts and a sulfur source, and connected to an electrochemical workstation. Amorphous transition metal sulfides are then deposited on the substrate using electrochemical cyclic voltammetry.

[0058] In a preferred embodiment, the operating parameters of the electrochemical cyclic voltammetry are: voltage range of -2 to 2V, scan rate of 2 to 10mV / s, and 10 to 15 cycles; the transition metal salt is a transition metal chloride salt with a concentration of 5 to 10mM; and the sulfur source is thiourea with a concentration of 0.5 to 1M.

[0059] Amorphous transition metal sulfides were deposited directly on the substrate of amorphous transition metal oxide nanotubes using cyclic voltammetry, which resulted in a tight bond between the nanospheres and nanotubes, which is beneficial for electron transport.

[0060] It should be understood that the methods for depositing amorphous transition metal sulfides on a substrate include, but are not limited to, electrochemical cyclic voltammetry. Other methods can also be used for deposition, such as electrochemical pulse deposition and hydrothermal methods.

[0061] In other preferred embodiments, an application of the aforementioned composite electrode for non-enzymatic glucose sensors is provided, which can be directly used as an electrode for glucose detection and has good catalytic performance.

[0062] To facilitate better understanding, the present invention will be further described below with reference to specific examples, but the preparation method is not limited thereto, and the content of the present invention is not limited thereto.

[0063] Unless otherwise specified, all raw materials used in the following examples were purchased commercially.

[0064]

Example 1

[0065] With Zr 56 Al 16 Co 28-x Ni x (x=5at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 9.2g of Co and 2g of Ni are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0066] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACN-O.

[0067] Using a ZACN-O electrode (0.4 cm × 0.5 cm) as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode, Ni-S / ZACN-O electrodes were electrochemically synthesized in an aqueous electrolyte containing 10 mM NiCl2 and 0.75 M thiourea in a range of -1.2 V to 0.2 V for 15 cycles (relative to SCE) at a scan rate of 5 mV / s.

[0068] The Ni-S / ZACN-O electrode was then rinsed with deionized water and alcohol and dried overnight in an air drying oven at 60°C.

[0069]

Example 2

[0070] With Zr 56 Al 16 Co 28-x Ni x (x=1at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 10.8g of Co and 0.4g of Ni are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0071] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACN-O.

[0072] A ZACN-O electrode (0.4 cm × 0.5 cm) was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. Cyclic voltammetry was employed to synthesize the Co-S / ZACN-O electrode electrochemically in an aqueous electrolyte containing 10 mM CoCl2 and 0.75 M thiourea for 10 cycles (relative to the SCE) within a range of -1.2 V to 0.2 V using a scan rate of 5 mV / s.

[0073] The Co-S / ZACN-O electrode was then rinsed with deionized water and alcohol and dried overnight in an air drying oven at 60°C.

[0074]

Example 3

[0075] With Zr 56 Al 16 Co 28-x Ni x(x=10at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 7.2g of Co and 4g of Ni are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0076] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACN-O.

[0077] A ZACN-O electrode (0.4 cm × 0.5 cm) was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. The Cu-S / ZACN-O electrode was electrochemically synthesized in an aqueous electrolyte containing 10 mM CuCl2 and 0.75 M thiourea for 15 cycles (relative to the SCE) at a scan rate of 5 mV / s within the range of -1.2 V to 1 V.

[0078] Subsequently, the Cu-S / ZACN-O electrode was rinsed with deionized water and alcohol and dried overnight in an air drying oven at 60°C.

[0079]

Example 4

[0080] With Zr 56 Al 16 Co 28-x Ni x (x=5at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 9.2g of Co and 2g of Ni are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0081] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACN-O.

[0082] A ZACN-O electrode (0.4 cm × 0.5 cm) was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. Cyclic voltammetry was employed to synthesize the Fe-S / ZACN-O electrode electrochemically in an aqueous electrolyte containing 10 mM FeCl2 and 0.75 M thiourea for 10 cycles (relative to the SCE) within a range of -2 V to 2 V using 5 mV / s scan rate.

[0083] Subsequently, the Fe-S / ZACN-O electrode was rinsed with deionized water and alcohol, and then dried overnight in an air drying oven at 60°C.

[0084]

Example 5

[0085] With Zr 56 Al 16 Co 28-x Ni x (x=5at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 9.2g of Co and 2g of Ni are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0086] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACN-O.

[0087] A ZACN-O electrode (0.4 cm × 0.5 cm) was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. Cyclic voltammetry was employed to synthesize the Mn-S / ZACN-O electrode electrochemically in an aqueous electrolyte containing 10 mM MnCl2 and 0.75 M thiourea for 15 cycles (relative to the SCE) within a range of -2 V to 2 V using cyclic voltammetry at a scan rate of 5 mV / s.

[0088] Subsequently, the Fe-S / ZACN-O electrode was rinsed with deionized water and alcohol, and then dried overnight in an air drying oven at 60°C.

[0089]

Example 6

[0090] With Zr 56 Al 16 Co 28-x Ni x(x=5at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 9.2g of Co and 2g of Ni are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0091] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACN-O.

[0092] A ZACN-O electrode (0.4 cm × 0.5 cm) was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. Ni-Co-S / ZACN-O electrodes were electrochemically synthesized in an aqueous electrolyte containing 10 mM CoCl2, 5 mM NiCl2, and 0.75 M thiourea in a range of -1.2 V to 0.2 V using cyclic voltammetry at a scan rate of 5 mV / s within the SCE range for 15 cycles. Subsequently, the Ni-Co-S / ZACN-O electrodes were rinsed with deionized water and alcohol and dried overnight in an air-drying oven at 60 °C.

[0093]

Example 7

[0094] With Zr 56 Al 16 Co 28-x Ni x (x=5at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 9.2g of Co and 2g of Ni are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0095] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACN-O.

[0096] Electrochemical cyclic voltammetry deposition was performed using a ZACN-O electrode as a substrate in a standard three-electrode cell. A ZACN-O electrode (0.4 cm × 0.5 cm) was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. Co-Cu-S / ZACN-O electrodes were electrochemically synthesized in an aqueous electrolyte containing 10 mM CoCl2, 5 mM CuCl2, and 0.75 M thiourea in a range of -1.2 V to 1 V using cyclic voltammetry at a scan rate of 5 mV / s. Subsequently, the Co-Cu-S / ZACN-O electrodes were rinsed with deionized water and alcohol and dried overnight in an air-drying oven at 60 °C.

[0097]

Example 8

[0098] With Zr 56 Al 16 Co 28-x Ni x (x=5at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 9.2g of Co and 2g of Ni are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0099] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACN-O.

[0100] Electrochemical cyclic voltammetry deposition was performed using a ZACN-O electrode as a substrate in a standard three-electrode cell. A ZACN-O electrode (0.4 cm × 0.5 cm) was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. Fifteen cycles (relative to SCE) were performed using cyclic voltammetry at a scan rate of 5 mV / s in the range of -2 V to 2 V to electrochemically synthesize Fe-Mn-S / ZACN-O electrodes in an aqueous electrolyte containing 10 mM FeCl2, 5 mM MnCl2, and 0.75 M thiourea. Subsequently, the Fe-Mn-S / ZACN-O electrode was rinsed with deionized water and alcohol and dried overnight in an air-drying oven at 60 °C.

[0101]

Example 9

[0102] With Zr 56 Al 16Co 28-x Ag x (x=5at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 9.2g of Co and 2g of Ag are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0103] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACA-O.

[0104] A ZACA-O electrode (0.4 cm × 0.5 cm) was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. Ni-Co-S / ZACA-O electrodes were electrochemically synthesized in an aqueous electrolyte containing 10 mM CoCl2, 5 mM NiCl2, and 0.75 M thiourea at a scan rate of 5 mV / s within the range of -1.2 V to 0.2 V for 15 cycles (relative to SCE). Subsequently, the Ni-Co-S / ZACA-O electrode was rinsed with deionized water and alcohol and dried overnight in an air-drying oven at 60 °C.

[0105]

Example 10

[0106] With Zr 56 Al 16 Co 28-x Nb x (x=5at.%) If the amorphous alloy is used as the precursor, then 22.4g of Zr, 6.4g of Al, 9.2g of Co and 2g of Nb are weighed and smelted to obtain a master alloy containing transition metals. The master alloy is then rapidly cooled and spun through copper rollers to obtain amorphous alloy strips.

[0107] Using an amorphous alloy strip as the working electrode (working area 0.4cm*0.5cm) and a Pt sheet as the counter electrode, anodization was performed in a mixed solution of 0.5MNH4F, 10% vol H2O, and glycerol for 30 min. The voltage output of the electrochemical workstation was set to 50V using a voltage amplifier. After anodization, the sample surface was thoroughly cleaned with ethanol and deionized water to remove any remaining solution. The sample was then dried at room temperature and stored under vacuum to obtain amorphous oxide nanotubes ZACNb-O.

[0108] A ZACNb-O electrode (0.4 cm × 0.5 cm) was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. Ni-Co-S / ZACNb-O electrodes were electrochemically synthesized in an aqueous electrolyte containing 10 mM CoCl2, 5 mM NiCl2, and 0.75 M thiourea at a scan rate of 5 mV / s within a range of -1.2 V to 0.2 V for 15 cycles (relative to SCE). Subsequently, the Ni-Co-S / ZACNb-O electrode was rinsed with deionized water and alcohol and dried overnight in an air-drying oven at 60 °C.

[0109] [Comparative Example]

[0110] In contrast to existing technologies that use amorphous metal oxides to detect glucose, titanium-based nanotubes (TiCu-O) were prepared and their catalytic performance was compared with that of the electrode material of this invention.

[0111] A classic two-electrode system is used, in which Ti 60 Cu 40 Amorphous strips were used as the working electrode (working area 0.2 cm * 1 cm), and Pt sheets were used as the counter electrode. Nanotube arrays were fabricated using an electrochemical anodic oxidation method. The solutions and parameters used in the experiment were as follows: the solution was a mixture of 0.15 wt% NH4F + 2.0 vol% H2O and ethylene glycol; the anodic oxidation time was 4 hours; and the voltage was 15 V. After anodic oxidation, the sample surface was thoroughly cleaned with ethanol and deionized water to remove residual solution, dried at room temperature, and stored under vacuum to obtain titanium-based nanotubes (TiCu-O).

[0112] SEM

[0113] The amorphous oxide nanotube ZACN-O and Ni-S / ZACN-O electrodes obtained in Example 1, and the Ni-Co-S / ZACN-O electrode obtained in Example 6 were subjected to SEM tests.

[0114] Morphology of amorphous oxide nanotubes ZACN-O as shown in the figure. Figure 1a As shown, a uniform nanotube structure was prepared and it was neatly arranged into a nanotube array structure.

[0115] Morphology diagram of Ni-S / ZACN-O electrode, as shown Figure 1b As shown, nanosphere clusters are uniformly deposited on the nanotubes.

[0116] The morphology of the Ni-Co-S / ZACN-O electrode is shown in Figure 1(ce). It can be seen that the nanotube (2# in 1e) is based on the corresponding amorphous transition metal alloy (1# in 1e), and nanosphere clusters (3# in 1e) are uniformly deposited on the nanotube.

[0117] And from Figure 1d It can be seen that these nanosphere clusters form a unique coral-like structure. This is because when transition metal sulfides are deposited, they grow upwards from the surface of the nanotubes, thus forming unique clusters of columnar structures, similar to a coral-like structure.

[0118] XRD

[0119] XRD tests were performed on the amorphous oxide nanotube ZACN-O and Ni-S / ZACN-O electrodes obtained in Example 1, and the Ni-Co-S / ZACN-O electrode obtained in Example 6.

[0120] Figure 2 The figures show the XRD patterns of amorphous oxide nanotube ZACN-O, Ni-S / ZACN-O, and Ni-Co-S / ZACN-O electrodes. As can be seen from the figures, all three electrodes exhibit broad and diffuse scattering peaks, and no other obvious crystalline diffraction peaks are observed. This indicates that the three electrodes exhibit typical amorphous characteristics, suggesting that all three electrodes are amorphous structures.

[0121] Catalytic performance

[0122] The amorphous oxide nanotubes ZACN-O and Ni-S / ZACN-O electrodes obtained in Example 1, the Co-S / ZACN-O electrode obtained in Example 2, the Ni-Co-S / ZACN-O electrode obtained in Example 6, and the TiCu-O electrode obtained in Comparative Example 1 were used as working electrodes, and their performance on glucose catalytic oxidation was tested using cyclic voltammetry and chronoamperometry.

[0123] Figure 3 (ad) shows the CV curves for the ZACN-O, Ni-S / ZACN-O, Co-S / ZACN-O, and Ni-Co-S / ZACN-O electrodes. It can be seen that all four electrodes exhibit redox peaks, proving that all four electrodes possess catalytic oxidation performance. The peak currents for the ZACN-O, Ni-S / ZACN-O, Co-S / ZACN-O, and Ni-Co-S / ZACN-O electrodes are approximately 1.5 mA / cm². 2 13mA / cm 2 13.5mA / cm 2 30mA / cm 2 It can be seen that the Ni-Co-S / ZACN-O electrode has the highest catalytic oxidation performance, and the catalytic performance is: ZACN-O electrode < Ni-S / ZACN-O electrode / Co-S / ZACN-O electrode < Ni-Co-S / ZACN-O electrode.

[0124] from Figure 3 (e) It can be seen that the peak current of the TiCu-O electrode is approximately 1.0 mA / cm. 2 The peak current is much lower than that of the Ni-S / ZACN-O, Co-S / ZACN-O and Ni-Co-S / ZACN-O electrodes, indicating that the electrode of the present invention has better catalytic performance.

[0125] Sensitivity, detection limit and detection range

[0126] Figure 4 The linear relationship between the current density response and glucose concentration caused by the drop of glucose in 0.1M NaOH at a potential of 0.55V is shown for different electrodes. The slope of the fit can be used to represent the sensitivity of the electrode to glucose. The inset shows the extremely significant current-time curve of glucose concentration changing with time.

[0127] from Figure 4 The properties of each material can be seen from (ae). The ZACN-O electrode has a sensitivity of 54 μM in the range of 0.1-2 mM. -1 cm -2 (R 2 =0.963), and the sensitivity can reach 4.3 μmM up to 2-9 mM. -1 cm -2 The detection limit is 3.2 μM.

[0128] The Ni-S / ZACN-O electrode achieves a sensitivity of 1285 μM in the range of 0.05-2 mM. -1 cm -2 (R 2 =0.999), and the sensitivity can reach 463 μmM up to 2-6 mM. -1 cm -2 The detection limit was 0.69 μM.

[0129] The Co-S / ZACN-O electrode achieves a sensitivity of 646 μM in the range of 0.05-2 mM. -1 cm -2 (R 2 =0.983), and the sensitivity can reach 373 μmM up to 2-6 mM. -1 cm -2 The detection limit was 1.36 μM.

[0130] The Ni-Co-S / ZACN-O electrode achieves a sensitivity of 2603 μM in the range of 0.01-0.5 mM. -1 cm -2 (R 2=0.984), and the sensitivity can still reach 723 μmM up to 0.5-6 mM. -1 cm -2 The detection limit was 0.34 μM.

[0131] The TiCu-O electrode achieves a sensitivity of 460 μM in the range of 0.2–3.2 mM. -1 cm -2 (R 2 =0.991), and the detection limit was 1.40 μM.

[0132] Therefore, it can be seen that the composite electrode for non-enzymatic glucose sensors of the present invention has better overall catalytic performance.

[0133] Detection of glucose concentration in human serum

[0134] Considering the practicality of the electrode of this invention, we applied the Ni-Co-S / ZACN-O electrode to the detection of glucose concentration in human serum.

[0135] Figure 5 The current response curves of glucose and serum being added sequentially to 0.1M NaOH solution at a potential of 0.55V are shown. The test results were compared with the concentrations provided by the hospital, as shown in Table 1. The measured glucose concentration in the serum sample (5.665 mM) was not significantly different from the hospital's result (5.62 mM), with a relative standard deviation (RSD) of 2.37%. This indicates that the composite electrode for non-enzymatic glucose sensors of the present invention can be used for the detection of glucose concentration in human serum and has great potential for clinical application.

[0136] Table 1

[0137]

[0138] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Those skilled in the art can make various modifications and refinements without departing from the spirit and scope of the invention. Therefore, the scope of protection of the present invention shall be determined by the claims.

Claims

1. A composite electrode for a non-enzymatic glucose sensor, characterized in that, The composite electrode has a composite structure formed by a double-layer nanostructure, which includes a bottom layer structure and a surface layer structure. The bottom layer structure is an amorphous transition metal oxide nanotube with one end face open. The surface layer structure is a nanostructure formed by depositing amorphous transition metal sulfides on the open end face of the amorphous transition metal oxide nanotube by electrochemical cyclic voltammetry. The nanostructure formed by the amorphous transition metal sulfides is a coral-like nanosphere cluster structure. The amorphous transition metal oxide nanotubes are amorphous ZrAlCoM-O nanotubes, where M is Ni, Ag, or Nb; in the nanostructures formed by amorphous transition metal sulfides, the transition metal is one or two of Ni, Co, Cu, Fe, and Mn.

2. A method for preparing a composite electrode for a non-enzymatic glucose sensor according to claim 1, characterized in that, Includes the following steps: Amorphous transition metal oxide nanotubes were prepared using an amorphous alloy containing transition metals as a precursor; wherein the precursor was Zr. 56 Al 16 Co 28-x M x M is Ni, Ag, or Nb, x = 1~10 at.%; Using amorphous transition metal oxide nanotubes as a substrate, amorphous transition metal sulfides are deposited on the substrate to obtain an amorphous transition metal oxide / transition metal sulfide composite electrode; wherein the transition metal in the amorphous transition metal sulfide is one or two of Ni, Co, Cu, Fe and Mn.

3. The method for preparing the composite electrode for a non-enzymatic glucose sensor according to claim 2, characterized in that, Amorphous transition metal oxide nanotubes were prepared by electrochemical anodic oxidation. The specific process was as follows: metal elemental materials corresponding to the precursor were weighed in proportion and smelted to obtain a master alloy containing transition metals. The master alloy was then rapidly cooled and spun through a copper roller to obtain an amorphous alloy strip. The amorphous alloy strip was then subjected to constant potential polarization treatment in an electrolyte and cleaned to obtain amorphous transition metal oxide nanotubes.

4. The method for preparing the composite electrode for a non-enzymatic glucose sensor according to claim 3, characterized in that, The electrolyte is a glycerol solution of 0.1~1 M NH4F + 5%~15% vol H2O, with a polarization potential of 30-60V and a polarization time of 10~40min.

5. The method for preparing the composite electrode for a non-enzymatic glucose sensor according to claim 2, characterized in that, Amorphous transition metal sulfides were deposited on a substrate using electrochemical cyclic voltammetry. The specific process was as follows: a three-electrode system was used, with an amorphous transition metal oxide nanotube as the working electrode, a Pt electrode as the counter electrode, and a saturated calomel electrode as the reference electrode. The working electrode, counter electrode, and reference electrode were placed in an aqueous solution containing transition metal salts and a sulfur source and connected to an electrochemical workstation. Amorphous transition metal sulfides were then deposited on the substrate using electrochemical cyclic voltammetry.

6. The method for preparing the composite electrode for a non-enzymatic glucose sensor according to claim 5, characterized in that, The operating parameters of the electrochemical cyclic voltammetry are: voltage range of -2 to 2V, scan rate of 2 to 10 mV / s, and 10 to 15 cycles; the transition metal salt is a transition metal chloride salt with a concentration of 5 to 10 mM; the sulfur source is thiourea with a concentration of 0.5 to 1 M.

7. The application of the composite electrode for a non-enzymatic glucose sensor as described in claim 1 in a non-enzymatic glucose sensor.